2019
DOI: 10.3390/app9183701
|View full text |Cite
|
Sign up to set email alerts
|

Grain Size Effects in Selective Laser Melted Fe-Co-2V

Abstract: The material science of additive manufacturing (AM) has become a significant topic due to the unique way in which the material and geometry are created simultaneously. Major areas of research within inorganic materials include traditional structural materials, shape memory alloys, amorphous materials, and some new work in intermetallics. The unique thermal profiles created during selective laser melting (SLM) may provide new opportunities for processing intermetallics to improve mechanical and magnetic perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Figure shows a comparison between the predicted coercivity using Equation () compared to measured coercivity and grain size from DED Fe49Co2V and wrought Fe49Co2V. The grain size and the corresponding coercivity for the low, medium, and high processed laser‐deposited material follow similar behavior, which is consistent with the reported data for both wrought and AM materials [ 24,25 ] and the generally accepted mechanism of grain boundaries acting as pinning agents and restricting domain wall movement.…”
Section: Resultssupporting
confidence: 82%
“…Figure shows a comparison between the predicted coercivity using Equation () compared to measured coercivity and grain size from DED Fe49Co2V and wrought Fe49Co2V. The grain size and the corresponding coercivity for the low, medium, and high processed laser‐deposited material follow similar behavior, which is consistent with the reported data for both wrought and AM materials [ 24,25 ] and the generally accepted mechanism of grain boundaries acting as pinning agents and restricting domain wall movement.…”
Section: Resultssupporting
confidence: 82%
“…Finally, H c decreased to 1.23 Oe at 90 nm. The amorphous structure of the Co 40 Fe 40 W 20 films indicated that the smaller H c was due to the small grain size distribution of the amorphous state when t f ranged from 18 to 42 nm [29][30][31][32]. The H c value was smaller than 2 Oe, suggesting the Co 40 Fe 40 W 20 films had soft magnetism, thus making them suitable for MRAM and recording head applications.…”
Section: Methodsmentioning
confidence: 99%
“…This might be attributed to the complete phase transformation, as above 1,422 K and up to the melting point (1,422 K ˂ T ˂ 1,713 K) ferrites form in the alloy [23]. Notably, the increase in formability of the material was proportional to the decrease in grain size of the heated sample [24][25][26]. The homogenized equiaxed fine grains in the microstructure were also associated with a decrease in anisotropy.…”
Section: Effects Of the Temperature And Microstructurementioning
confidence: 96%